2017
DOI: 10.1002/ccd.26973
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study of the impella device for mechanical support of the systemic circulation in pediatric and adolescent patients

Abstract: Objectives The objective was to review the use of Impella devices (Abiomed Inc, Danvers, MA) for temporary circulatory support in pediatric and adolescent patients (age ≤21 yrs). Background Options for minimally invasive circulatory support in children are limited, and published data are confined to case reports and small case series. Methods This was a retrospective, multicenter review of Impella implants in pediatric and adolescent patients from 2009–15, using standardized data collection and INTERMACS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 23 publications
0
49
0
1
Order By: Relevance
“…In the largest pediatric study, serious adverse events were uncommon. The most common adverse events reported in this study were hemolysis ( n = 3) and access related complications ( n = 2) . More experience and data are necessary to further understand the boundaries of this technology in pediatric patients.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In the largest pediatric study, serious adverse events were uncommon. The most common adverse events reported in this study were hemolysis ( n = 3) and access related complications ( n = 2) . More experience and data are necessary to further understand the boundaries of this technology in pediatric patients.…”
Section: Discussionmentioning
confidence: 91%
“…There are limited temporary MCS options for pediatric patients. Recent studies of the Impella microaxial pump in pediatric and adolescent patients demonstrated that younger patients can be supported with this device . Although a patient as small as 15 kg was supported in that study, the average patient was closer to adult size and there remain questions about the smallest patients that can be safely supported with this technology.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies confirm the successful application of such devices . However, several potential complications were reported, such as increase in aortic regurgitation during cardiac support, aortic or mitral valve damage, or thrombus formation . Transvalvular pumps have even been used in combination with biologic and transcatheter aortic valve replacements …”
Section: Introductionmentioning
confidence: 99%